Penerapan Tools Integrasi Perencanaan Produksi Pada Departemen Production Planning and Inventory Control PT. FSCM Manufacturing Indonesia - Alvin Liman; TANTI OCTAVIA (Jurnal Titra, 2015)
The purpose of this study was to determine the impact of integrated production planning to PPIC Department. Main problems of PT. FSCM Manufacturing Indonesia were the high cost of Heat Treatment Workstation and the loss of control from PPIC Department to manufacturing area. The high cost of Heat Treatment Workstation caused by the setup time/ dandori time of each type of component being processed. The daily production load resulted in repetition of setup time/ dandori time. The loss of control from PPIC Department to manufacturing area also caused higher level of WIP components resulted in the holding cost of this WIP components. Improvement given was to implement new production planning system with daily production load around 10 days in Heat Treatment Workstation and take a control to PPIC Department in manufacturing area .The results showed that integrated production planning to PPIC Department could reduce manufacturing cost of Heat Treatment Workstation and reduce the WIP levels. The reduction of production cost at Heat Treatment Workstation is about Rp. 236.448.747,00. The reduction of WIP levels could give the potential benefit around  Rp. 2.984.382,53.